Feasibility Analysis of Hydrophonic Vegetables Bussiness in Cempako Vegetable Villages, 26 Ilir, Palembang City - Hati, Pamela Felita; Sjarkowi, Fachrurrozie (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2022)
The combination of shrinking land and facing pandemic conditions like this raises the idea of being able to solve existing problems by growing vegetables on limited land using hydroponic systems. One form of application of hydroponic cultivation systems on limited land by utilizing vacant land in the yard is applied in Cempako vegetable village 26, Ilir, Palembang city. The 20 respondents who were used as samples were all members of the Cempako vegetable village group who worked in the hydroponic vegetable section in Cempako vegetable village 26, Ilir, Palembang city, consisting of 20 people. The objectives of this study are: (1) to describe the feasibility of a hydroponic vegetable business in Kampung Sayur Cempako based on legal aspects; environmental aspects; market and marketing aspects; technical and technological aspects; aspects of management and human resources; and economic and social aspects (2) Use financial feasibility assessment criteria such as Net Present Value, Internal Rate of Return, Benefit Cost Ratio, Gross Benefit Cost Ratio, and Payback Period to assess the financial feasibility of the hydroponic vegetable business in Kampung Sayur Cempako, 26 Ilir, Palembang. (3)sensitivity analysis of a hydroponic vegetable business in Cempako vegetable village, Ilir, Palembang City. The study's findings are (1) non-financial business feasibility criteria, which include legal aspects, market and marketing aspects, technical and technological aspects, management and human resource aspects, environmental aspects, and feasible social and economic aspects. (2) business feasibility criteria based on financial aspects obtained a Net Present Value (NPV) positive value of RP of 2.939.786,000.00. In a 5-year analysis period, the value of Net B/C 3.38 and Gross B/C 1.4 is greater than 1. The internal rate of return (IRR) is greater than the interest rate of 6%, which is 33.14 percent, and the payback period obtained is 9 months and 4 days. Then the overall criteria for the financial feasibility of hydroponic vegetable cultivation in Kampung Sayur Cempako are feasible. (3) hydroponic vegetable business in Kampung Sayur Cempako must be developed based on sensitivity analysis if there is a change in production costs consisting of changes in investment costs by 3 percent and changes in operational costs by 7 percent. If production increases by more than 3% of investment costs and 7% of operational costs, the business is no longer feasible to run.